Modeling Metamorphic Rocks Using Equilibrium Thermodynamics and Internally Consistent Databases: Past Achievements, Problems and Perspectives - Lanari, Pierre; Duesterhoeft, Erik (Journal of petrology, 2019)
Abstract The astonishing progress of personal computer technology in the past 30 years as well as the availability of thermodynamic data and modeling programs have revolutionized our ability to investigate and quantify metamorphic processes. Equilibrium thermodynamics has played a central role in this revolution, providing simultaneously a physico-chemical framework and efficient modeling strategies to calculate mineral stability relations in the Earth’s lithosphere (and beyond) as well as thermobarometric results. This Perspectives contribution provides a review of the ingredients and recipes required for constructing models. A fundamental requirement to perform thermodynamic modeling is an internally consistent database containing standard state properties and activity–composition models of pure minerals, solid solutions, and fluids. We demonstrate how important internal consistency is to this database, and show some of the advantages and pitfalls of the two main modeling strategies (inverse and forward modeling). Both techniques are commonly applied to obtain thermobarometric estimates; that is, to derive P–T (pressure–temperature) information to quantify the conditions of metamorphism. In the last section, we describe a new modeling strategy based on iterative thermodynamic models, integrated with quantitative compositional mapping. This technique provides a powerful alternative to traditional modeling tools and permits use of local bulk compositions for testing the assumption of local equilibrium in rocks that were not fully re-equilibrated during their metamorphic history. We argue that this is the case for most natural samples, even at high-temperature conditions, and that this natural complexity must be taken into consideration when applying equilibrium models.